Influence of Intellectual Capital, Capital Structure and Firm Size on Financial Performance of PT XL Axiata Tbk - Cindy Dwi Alvionita; Umar Farouk; Subandi (Politeknik Negeri Semarang, 2025)
Profitability is important for companies to measure the company's ability to generate profits. The decline in profitability encourages companies to understand the factors that can influence it. This research is conducted to examine and explain the effect of Intellectual Capital, Capital Structure, and Company Size on the Financial Performance of PT XL Axiata Tbk. In this study, the intellectual capital was measured by using the VAIC method, the capital structure was proxied by Debt to Assets Ratio (DAR), firm size was calculated by using the logarithm of total assets, and financial performance was proxied by Return on Assets (ROA). This type of study is explanatory research using a quantitative approach. The data were analyzed using multiple linear regression supported by IBM SPSS Statistic 25. The results of this study indicate that variable intellectual capital and firm size partially have a significant effect on ROA. Meanwhile, capital structure (DAR) has no significant effect on the ROA of PT XL Axiata Tbk. Based on the determination coefficient, intellectual capital, capital structure, and firm size have an influence on ROA of PT XL Axiata Tbk by 82,1%. Meanwhile, the remaining 17,9% is influenced by other variables which are not examined in this research. Profitabilitas penting bagi perusahaan untuk mengukur kemampuan perusahaan menghasilkan laba. Penurunan profitabilitas mendorong perusahaan untuk memahami faktor-faktor yang dapat mempengaruhinya. Tujuan utama dari penelitian ini adalah untuk menguji dan menjelaskan pengaruh Modal Intelektual, Struktur Modal, dan Ukuran Perusahaan terhadap Profitabilitas PT XL Axiata Tbk. Dalam penelitian ini, modal intelektual diukur dengan metode VAIC, struktur modal diproksikan dengan Debt to Assets Ratio (DAR), ukuran perusahaan dihitung dengan menggunakan logaritma dari total aset, dan kinerja keuangan diproksikan dengan Return on Assets (ROA). Jenis penelitian ini adalah explanatory research dengan menggunakan pendekatan kuantitatif. Hasil dari penelitian ini menunjukkan bahwa variabel modal intelektual dan ukuran perusahaan secara parsial berpengaruh signifikan terhadap ROA. Sedangkan struktur modal (DAR) tidak berpengaruh signifikan terhadap ROA PT XL Axiata Tbk. Berdasarkan koefisien determinasi, modal intelektual, struktur modal, dan ukuran perusahaan berpengaruh terhadap ROA PT XL Axiata Tbk sebesar 82,1%. Sedangkan sisanya sebesar 17,9% dipengaruhi oleh variabel lain yang tidak diteliti dalam penelitian ini